STABILIZATION OF DRY SLUDGE OF LIQUID WASTE OF LEATHER TREATMENT BY USING FLY ASH - Cahya Widiyati; Herry Poernomo (Universitas Gadjah Mada, 2005)
The experiment of solidification of dry sludge of liquid waste of leather treatment are containing chrome (Cr) by using fly ash has been done. The experiment objective are immobilize Cr in the solid waste by using pozzoland cement was made of fly ash in order to stable in the repository. The experiment were carried out by solidification of solid waste are containing total chrome of 1480.5 mg/kg sum of 2 - 10 weight % of (water + pozzoland cement) by using pozzoland cement was made from the mixture of fly ash and calcite were burned at 1000 oC temperature for 2 hours. The characterization of the solid composite of stabilization result consist of the compressive strength test and the leaching test by American Nuclear Society (ANS-16.1) method. The experiment result were shown that pozzoland cement can binding solid waste sum of 10 weight % of (water + pozzoland cement) became the composite of waste concrete with the compressive strength of 577 ton/m2 and the chrome leaching test for 14 days of 0.059 mg/l. The composite of waste concrete according to Bapedal rule for solidification of toxic waste with minimum compressive strength of 10 ton/m2 and maximum leached chrome of 5 mg/L.